Improving Speaking Skills through Online-Based Interactive Picture Media in Elementary Schools - Pipit Rahmadhany; Esti Untari; Sri Kustiyah (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2022)
The COVID-19 pandemic has had an unfavorable impact on all aspects of life, including aspects of health, economy, tourism, social and education. Students can also use learning support applications such as study houses, teacher rooms, thinglink, netboard, oodlu, quizwhizzer and other applications. In fact, not all students will be successful in online learning. This research aims to improve speaking skills through the application of online-based interactive picture media to 5th graders at SD Negeri 2 Blitaran, Nganjuk Regency. This research is a classroom action research with the research design determined are planning, implementation, observation and reflection. There are two data obtained, namely process data and result data. Process data obtained from teacher activity data and student activities in applying online-based interactive image media. Result data obtained from student learning outcomes data in the form of students' speaking skill scores through the application of online-based interactive image media. The research subjects were 31 fifth grade students at SD Negeri 2 Blitaran, Nganjuk Regency, for the 2020/2021 academic year. The results showed that the teacher's activities continued to increase starting from the pre-action cycle II. In the pre-action, the average score of students was only 63.1 with a very poor category. After taking action in cycle 1 at meeting 1, the average score of students increased to 80%. The percentage of 80% indicates that there are still activities that have not been carried out at meeting 1. The action is continued in the second friendship, where the ability of students has reached 87%. With this percentage, improvements need to be made in cycle II. The teacher must review the steps in the lesson plans that have been prepared so that learning can run according to the plan. In Cycle II meeting 1, the percentage of success was 92.8%. The thing that must be maintained in cycle II is that the teacher carries out learning according to the steps that have been planned and provides explanations to students regarding important things that must be considered when retelling a reading. The action was continued in Cycle II meeting 2 where the student success achieved reached 95.7%. This happens because the teacher carries out learning in accordance with the planned RPP based on the results of the cycle reflection. Teachers should emphasize